Analysis Of The Use HSD, MDO And B-30 On Passenger Ships 2000 GT - Oloan, Aldyn Clinton Partahi; Muslim, Muswar; Buwono, Ayom; Febrian, Shahrin (International Journal of Marine Engineering Innovation and Research, 2025)
The ship being analyzed is a Ferry ro-ro 2000 GT sailing from Bali to Lombok via the Lombok Strait crossing route with a distance of 38 nautical miles. Identification of the use of diesel fuel for ship operations is important for ferry vessels, especially in connection with efforts to efficiently use of diesel fuel in ship operations. In solving problems, efficiency analysis is completed by applying technical analytical, correlational-predictive, and comparative methods. The technical analytical method is specifically used to calculate engine characteristics in fuel use, and the correlational-predictive method is used as an approach method to the phenomenon of the relationship between engine characteristics in the use of different fuels in ship operations, in contrast, the comparative method approach will be used to provide a detailed illustration. More complete in a case study of the use of diesel as fuel for the operational main engine of a ferry ship.